2015
DOI: 10.1186/s12920-015-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of next-generation sequencing and array comparative genomic hybridization for preimplantation genetic screening: a pilot study

Abstract: BackgroundRecent advances in next-generation sequencing (NGS) have provided new methods for preimplantation genetic screening (PGS) of human embryos from in vitro fertilization (IVF) cycles. However, there is still limited information about clinical applications of NGS in IVF and PGS (IVF-PGS) treatments. The present study aimed to investigate the effects of NGS screening on clinical pregnancy and implantation outcomes for PGS patients in comparison to array comparative genomic hybridization (aCGH) screening.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 54 publications
3
41
0
1
Order By: Relevance
“…In addition to array CGH analysis, we also explored the use of whole shotgun NGS to determine copy number as is commonly applied to embryonic cells for preimplantation genetic screening. 28,29 We aimed to obtain about 5 million NGS reads per cell. Paired-end sequencing reads were obtained for each sample.…”
Section: Single Cell Next-generation Sequencingmentioning
confidence: 99%
“…In addition to array CGH analysis, we also explored the use of whole shotgun NGS to determine copy number as is commonly applied to embryonic cells for preimplantation genetic screening. 28,29 We aimed to obtain about 5 million NGS reads per cell. Paired-end sequencing reads were obtained for each sample.…”
Section: Single Cell Next-generation Sequencingmentioning
confidence: 99%
“…= partial chromosome gain or loss (length in Mb). when embryonic biopsies are analysed during preimplantation genetic diagnosis [Fiorentino et al, 2014;Yang et al, 2015]. We subsequently performed a validation study of our NGS-based protocol by a comparison of metaphase-CGH and NGS results from the same WGA product of the previously analysed porcine blastomeres using metaphase-CGH [Hornak et al, 2015].…”
Section: Ngs Protocolmentioning
confidence: 99%
“…Interestingly, with regard to their reason for wanting PGT‐A, significantly more patients who self‐assessed as knowing well or knowing a little about PGT‐A chose the “to give live birth” and not the “to avoid miscarriage” option. Indeed, several RCTs showed that PGT‐A improved the live birth rate and reduced miscarriage in a limited number of infertile patients with a favorable prognosis . However, in one study, PGT‐A did not improve the live birth rate or reduce the miscarriage rate in RPL patients .…”
Section: Discussionmentioning
confidence: 98%
“…However, there has been controversy regarding whether it can improve the live birth rate and prevent miscarriage in patients with RPL or aid infertile patients, although PGT‐A was originally developed in order to prevent miscarriage caused by aneuploidy at an advanced maternal age. With the progress made in scientific technologies such as array comparative genomic hybridization (aCGH), next generation sequencing (NGS) and trophectoderm biopsy, several randomized control trials (RCT) revealed that PGT‐A improved the live birth rate in limited populations with a favorable prognosis . However, several RCTs demonstrated no improvement in the live birth rate from its use .…”
Section: Introductionmentioning
confidence: 99%